Improved adsorption of the toxic herbicide diuron using activated carbon obtained from residual cassava biomass (manihot esculenta) (2022)
The production and consumption of cassava (Manihot esculenta) occur in several places worldwide, producing large volumes of waste, mostly in the form of bark. This study sought to bring a new purpose to this biomass through producing activated carbon to use as an adsorbent to remove the herbicide Diuron from water. It was observed that the carbon contains the functional groups of methyl, carbonyl, and hydroxyl in a strongly amorphous structure. The activated carbon had a surface area of 613.7 m2 g−1, a pore volume of 0.337 cm3 g−1, and a pore diameter of 1.18 nm. The Freundlich model was found to best describe the experimental data. It was observed that an increase in temperature favored adsorption, reaching a maximum experimental capacity of 222 mg g−1 at 328 K. The thermodynamic parameters showed that the adsorption was spontaneous, favorable, and endothermic. The enthalpy of adsorption magnitude was consistent with physical adsorption. Equilibrium was attained within 120 min. The linear driving force (LDF) model provided a strong statistical match to the kinetic curves. Diffusivity (Ds) and the model coefficient (KLDF) both increased with a rise in herbicide concentration. The adsorbent removed up to 68% of pollutants in a simulated effluent containing different herbicides. Activated carbon with zinc chloride (ZnCl2), produced from leftover cassava husks, was shown to be a viable alternative as an adsorbent for the treatment of effluents containing not only the herbicide Diuron but also a mixture of other herbicides.